2008
DOI: 10.3928/15394492-20090611-04
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Childhood Cancer, Participation, and Quality of Life of Adolescents

Abstract: This study investigated the late effects of childhood cancer on participation and quality of life. Ninety-two percent of survivors (9 to 18 years of age) reported living with late effects of lower extremity pain and numbness, memory and attention deficits, and fatigue, depression, or both. Semistructured interviews with 25 survivors using the Canadian Occupational Performance Measure and the Adolescent Activity Card Sort captured frequencies, interests, and barriers for a range of activities. Survivors reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
(41 reference statements)
0
15
0
2
Order By: Relevance
“…The reduced satisfaction with 'leisure time/ hobbies' might be a result of the restricted participation in physical activities, which has recently been demonstrated in subgroups of survivors of childhood cancer [15,53]. In addition, a study with adolescent survivors of childhood cancer showed a diminished engagement in leisure and community activities, which has also been associated with a lower QoL in this population [54].…”
Section: Discussionmentioning
confidence: 96%
“…The reduced satisfaction with 'leisure time/ hobbies' might be a result of the restricted participation in physical activities, which has recently been demonstrated in subgroups of survivors of childhood cancer [15,53]. In addition, a study with adolescent survivors of childhood cancer showed a diminished engagement in leisure and community activities, which has also been associated with a lower QoL in this population [54].…”
Section: Discussionmentioning
confidence: 96%
“…It affects children and adolescents with cancer at all stages of the disease trajectory from diagnosis to survivorship and the end-of-life period [4][5][6][7][8][9][10][11][12][13][14][15]. Fatigue has physical, mental, and emotional components and may be characterized by a lack of energy, decreased physical ability, and feelings of tiredness.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple articles explored the role (or potential role) of occupational therapists within cancer care at differing stages of the disease, highlighting limitations to the roles (Johnson, ; Lemoignan, Chasen, & Bargava, ; He‐‐Strocchio & Longpre, ), or gaps in services, mainly for the paediatric and adolescent populations (Berg, Neufeld, Harvey, Downes, & Hayashi, ; Briskey, Powderly, Richardson, & Atkinson, ). Return to work post‐cancer was also a topic in a number of papers.…”
Section: Resultsmentioning
confidence: 99%